Taking agile development beyond software – what are the security risks?. (December 2015) - Caldwell, Tracey
Abstract : The risks associated with developing software following agile methods have been a subject for discussion for some time and continue to evolve. And agile development methods are no longer just confined to software development. Tracey Caldwell highlights the risks arising from the agile approach – characterised by incremental, iterative work cadences – and addresses concerns that the customer or product owner focus of agile methods may compromise network security, as these major stakeholders are not generally prioritising security. The security risks associated with developing software following agile methods have been a subject for discussion for some time and continue to evolve. In addition, agile development methods are no longer just confined to software development and may be used to develop any number of web or IT-dependent products and services too that are interdependent with the network security of an enterprise.